2021
DOI: 10.1155/2021/5353785
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous Nerve Injury Resulted Erectile Dysfunction and Regeneration

Abstract: Erectile dysfunction (ED) is an important cause of reduced quality of life for men and their partners. Recent studies have found that cavernous nerve injury (CNI) during prostate cancer surgery and other pelvic surgery results in medically induced CNIED in more than 80% of patients. The efficacy of first- and second-line treatment options for ED is poor. A great deal of research has been devoted to exploring new methods of neuroprotection and nerve regeneration to save erectile function in patients with CNIED,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Moreover, its safety is very high, and so far there are few reports of adverse effects ( Pai et al, 2021 ). There is increasing evidence that Li-ESWT causes minor damage to vital organs such as the heart while improving myocardium, bladder, joints, and penis function ( Jiang et al, 2021 ).…”
Section: Physical Therapy Of Edmentioning
confidence: 99%
“…Moreover, its safety is very high, and so far there are few reports of adverse effects ( Pai et al, 2021 ). There is increasing evidence that Li-ESWT causes minor damage to vital organs such as the heart while improving myocardium, bladder, joints, and penis function ( Jiang et al, 2021 ).…”
Section: Physical Therapy Of Edmentioning
confidence: 99%
“…Prostate cancer surgery and other pelvic surgeries often result in damages to the cavernous nerve, which originates from the major pelvic ganglion (MPG) and controls the relaxation and contraction of CCSMCs, thus regulating the erection of the penis ( 71 ). It was reported that up to 80% of prostate cancer patients suffer from ED after radical prostatectomy ( 72 ).…”
Section: The Therapeutic Potential Of Exosomes In Edmentioning
confidence: 99%
“…Thus, currently, especially when tumor loco-regional extension allows for the use of a nerve-sparing RP technique, postoperative functional recovery has become the most important surgical goal. Due to the predisposing inherent regional pelvic anatomy, even in the hands of the most experienced surgeon, regardless of surgical technique or approach used, a certain degree of CN damage usually occurs during RP [ 10 ]. Additional strategies are required to improve EF outcomes after RP, seeing as contemporary treatment modalities, i.e., penile rehabilitation protocols, only provide a quicker recovery of EF, not a better rate of recovery overall [ 11 ].…”
Section: Introductionmentioning
confidence: 99%